2002
DOI: 10.1897/1551-5028(2002)021<1864:doafrg>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Fish Reporter Gene System for the Assessment of Estrogenic Compounds and Sewage Treatment Plant Effluents

Abstract: This study reports on the development and application of a fish-specific estrogen-responsive reporter gene assay. The assay is based on the rainbow trout (Oncorhynchus mykiss) gonad cell line RTG-2 in which an acute estrogenic response is created by cotransfecting cultures with an expression vector containing rainbow trout estrogen receptor a complementary DNA (rtERalpha cDNA) in the presence of an estrogen-dependent reporter plasmid and an estrogen receptor (ER) agonist. In a further approach, RTG-2 cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 46 publications
3
13
2
2
Order By: Relevance
“…To our knowledge, however, the present study is the first to report the antagonistic behavior of ZM 189154 in rainbow trout primary hepatocytes. However, these results also agree with those of recent studies using rainbow trout ER␣-specific reporter gene systems in rainbow trout gonad or hepatoma cell lines [34,35] and with studies in rats demonstrating the antagonistic behavior of ZM 189154 in uterus, vagina, bone, and on luteinizing hormone secretion and growth rate [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, however, the present study is the first to report the antagonistic behavior of ZM 189154 in rainbow trout primary hepatocytes. However, these results also agree with those of recent studies using rainbow trout ER␣-specific reporter gene systems in rainbow trout gonad or hepatoma cell lines [34,35] and with studies in rats demonstrating the antagonistic behavior of ZM 189154 in uterus, vagina, bone, and on luteinizing hormone secretion and growth rate [19].…”
Section: Discussionsupporting
confidence: 91%
“…The sensitivity of the reporter gene bioassay described in the present study was lower than that observed for the same reporter gene bioassay configuration using the chimeric human ER␣ [21,22] and with an ER reporter gene bioassay using the rainbow trout gonad cell line (RTG-2) [34]. The detection limit in the present study using the rainbow trout ER␣ construct was 10 nM E 2 , whereas the human ER construct has a detection limit of 0.01 nM and a maximum response at 1 nM [22].…”
Section: Discussioncontrasting
confidence: 69%
“…Largescale sucker from Station 506 also contained traces (0.01 μg/g) of o,p′-DDE and o,p′-DDD. Like many other pesticides and their metabolites, o,p′-DDD is weakly estrogenic even though the o,p′-homologs have historically been considered relatively benign (Guillette et al, 1996;Toppari et al, 1996;Tyler et al, 1998;Ackerman et al, 2002). The cumulative risk to fish and wildlife represented by concentrations of o,p′-DDT is unknown.…”
Section: Sub-basin and Stationmentioning
confidence: 99%
“…343 (Berthois et al, 1986). In 365 addition, serum deprivation during treatment resulted in weaker reporter gene induction when cells 366 were exposed to E2, again as previously reported (Ackermann et al, 2002). Moreover, the lack of 367 serum appears to affect cell fitness since they are not able to overcome the high concentrations of 368 fish feed extracts, resulting in cytotoxicity.…”
Section: Estrogenic Activity Of Sewage Water 274mentioning
confidence: 57%